Experimental and Numerical Studies on Sloshing Dynamics of PCS Water Tank of Nuclear Island Building - Xiaojun Li; Chenning Song; Guoliang Zhou; Chao Wei; Ming Lu (Science and Technology of Nuclear Installations)
Water tank is one important component of passive containment cooling system (PCS) of nuclear island building. The sloshing frequency of water is much less than structure frequency and large-amplitude sloshing occurs easily when subjected to seismic loadings. Therefore, the sloshing dynamics and fluid-structure interaction (FSI) effect of water tank should be considered when the dynamic response of nuclear island building is analyzed. A 1/16 scaled model was designed and the shaking table test was done, in which the hydrodynamic pressure time histories and attenuation data of wave height were recorded. Then the sloshing frequencies and 1st sloshing damping ratio were recognized. Moreover, modal analysis and time history analysis of numerical model were done by ADINA software. By comparing the sloshing frequencies and hydrodynamic pressures, it is proved that the test method is reasonable and the formulation of potential-based fluid elements (PBFE) can be used to simulate FSI effect of nuclear island building.